FERTILIDADE DE VACAS DE CORTE EM PROTOCOLOS DE SINCRONIZAÇÃO COM DIFERENTES INDUTORES DE OVULAÇÃO - nathalia albaneze anache (2023)
Despite the evident advances in the production of beef cattle, conferred by the commercial development of the IATF, the expected average pregnancy rate is estimated between 40 and 50%, and several factors may be related to these indices, highlighting those inherent to the female, such as postpartum anestrus and body condition. Brazilian producers generally inseminate all cows, regardless of whether the cow expresses estrus, even with studies indicating that estrus expression near FTAI is associated with greater fertility. Thus, this work evaluated strategies for improving pregnancy rates of beef cows, submitted to FTAI protocols with simple estrus evaluations (ESCT), follicular dynamics and application of two different additional ovulation inducers (GnRH and hCG). First, different doses of hCG were tested to see which would be more effective. Nellore females (n=45) were submitted to the FTAI protocol. The animals that showed little or no heat (ESCT 2 and 1, respectively) were divided into three groups on the day of insemination: control (n=11): 1 ml of, I.M., regulatory solution, group 500 IU (n= 12): application of 500 IU, I.M. of hCG and 1000 IU group (n=12): application of 1000 IU, I.M. of hCG. Cows that showed ESCT 3 (n=10) were inseminated at the same time, without the application of additional treatment. After 07 days of FTAI, follicular dynamics was evaluated by transrectal ultrasonography to assess the time of ovulation (mean time and ovulation rate) and CL area (cm³). The pregnancy diagnosis was around 30 days after FTAI. There was no statistical difference between the groups, except for the mean ovulation time, which was lower in the ESCT 3 group. After, 2.315 Nellore females were evaluated and, in the same way, ESCT 2 and 1 animals were divided into three groups, on the day of insemination: control (n=301): did not receive any treatment, GnRH (n=265): application of 0.1 mg, I.M. of Gonadorelin and hCG (n=267): application of 1000 IU, I.M. of hCG. ESCT 3 cows (n= 1483) were inseminated at the same time, without application of additional treatment. A pregnancy diagnosis was made approximately 35 days after FTAI (with mode B ultrasound). Animal pregnancy rates were evaluated to compare the effects of ovulation inducers and there was no statistical difference (P <0.001) between the GnRH (48.3%) and hCG (53.05%) groups, both of which were effective in the induction of ovulation in animals that gave little or no heat (ESCT 1 and 2), increasing pregnancy rates when compared to the control group. Keywords: Follicular dynamics, GnRH, hCG, marker stick.